The relation between management fees and the mutual funds` performance in Poland in 2015 - Alicja Fraś (Oeconomia Copernicana, 2018)
Research background: The investor`s expectation of better performance in the case of more expensive mutual funds seems natural and fully justified. However, the rise of passive funds and their surprisingly good results, especially when taking into account their low fees, triggered the discussion. Recent years have brought more and more studies, conducted mostly for the American market, discrediting high-charging, aggressive funds. First analyses in Poland also indicate that the level of fees is not always linked with the fund’s performance.